New Approach To Understanding the Experimental 133Cs NMR Chemical Shift of Clay Minerals via Machine Learning and DFT-GIPAW Calculations - Ohkubo, Takahiro; Takei, Akihiro; Tachi, Yukio; Fukatsu, Yuta; Deguchi, Kenzo; Ohki, Shinobu; Shimizu, Tadashi (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2023)
Structural determination of adsorbed atoms on layered structures such as clay minerals is a complex subject. Radioactive cesium (Cs) is an important element for environmental conservation, so it is vital to understand its adsorption structure on clay. The nuclear magnetic resonance (NMR) parameters of 133Cs, which can be determined from solid-state NMR experiments, are sensitive to the local neighboring structures of adsorbed Cs. However, determining the Cs positions from NMR data alone is difficult. This paper describes an approach for identifying the expected atomic positions on clay minerals by combining machine learning (ML) with experimentally observed chemical shifts. A linear ridge regression model for ML is constructed from the smooth overlap of atomic position descriptor and gauge-including projector augmented wave (GIPAW) ab initio data. The constructed ML model predicts the GIPAW data to within a 3 ppm root-mean-squared error. At this stage, the 133Cs chemical shifts can be instantaneously calculated from the Cs positions on any clay layers using ML. The inverse analysis, which derives the atomic positions from experimentally observed chemical shifts, is developed from the ML model. The input data for the inverse analysis are the layer structure and the experimentally observed chemical shifts. The Cs positions for the targeted chemical shifts are then output. Inverse analysis is applied to montmorillonite, and the resultant Cs positions are found to be consistent with previous results (Ohkubo, T.; et al. J. Phys. Chem. A 2018, 122, 9326–9337). The Cs positions on saponite clay are also clarified from experimentally observed chemical shifts and inverse analysis.